Management of complex growing teratoma syndrome in non seminomatous germ cell tumor: A Case Report with review of literature - Tiwari, Manoj; Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee (Nepalese Journal of Cancer, 2025)
Background: Mediastinal teratoma is an uncommon disease, nevertheless they represent the most common mediastinal germ cell tumors. These tumors occur equally in men and women are generally benign, all forms of these tumors have a peak incidence in young adults. Determination of serum tumor markers (alpha-fetoprotein AFP and human beta-choriogonadotropin B-HCG) is important in the diagnosis and follow-up of mediastinal teratoma.Case: A 24-year-old female had dull left sided chest pain, found to have large anterior mediastinal mass with mature teratoma histopathology on core biopsy but high AFP and B-HCG level. She received neoadjuvant cisplatin-based chemotherapy. Despite 3 cycles of therapy, her tumor size slightly increased but tumor markers level decreased. She underwent en block resection, postoperative course was uncomplicated. Her final pathology demonstrated mature teratoma.Conclusions: This case report highlights the case of young female with pathological diagnosis of mature teratoma but raised tumor markers, which lead towards the suspicion of malignant component. This pattern leads to dilemma for proceeding to upfront surgery or neo-adjuvant chemotherapy.